Pengaruh Tutupan Lahan Terhadap Sambaran Petir Cg (Cloud To Ground) di Wilayah Balikpapan, Kutai Kartanegara dan Penajam Paser Utara Pada Tahun 2015 – 2019 - Ramadhani, Fika Desy; Djayus, Djayus; Supriyanto, Supriyanto (GEOSAINS KUTAI BASIN, 2024)
The increasing number of residents in the Balikpapan, Kutai Kartanegara and North Penajam Paser areas demands the use of land for settlements, resulting in a decrease in green open land and the potential to increase lightning strikes. The purpose of this study was to determine the density of CG (Cloud to Ground) lightning strikes and the effect of land cover on CG (Cloud to Ground) lightning in the Balikpapan, Kutai Kartanegara and North Penajam Paser areas in 2015-2019. This study uses data from 2015-2019 lightning strikes obtained from BMKG Balikpapan. Furthermore, the 2015-2017 data was processed using the LD2000 software and the 2018-2019 data had begun to be processed using the NexStorm V.8.4 software, so that the lightning strike density was obtained. Land cover data for 2015-2019 was obtained from BPKH Samarinda, then analyzed to produce a land cover classification. Furthermore, it is correlated so as to produce the effect of land cover on lightning strikes. The results show that the highest lightning density in the Balikpapan area is located in South Balikpapan District in 2019 with a value of 171.04 with land cover dominated by residential areas and airports, the high lightning strikes in this area are due to tall buildings being a medium for lightning to reach the earth. . The North Penajam Paser area has the highest lightning density located in Waru sub-district in 2019 with a value of 41.31 with land cover dominated by secondary dry land forest and plantation forest areas. The Kutai Kartanegara region has the highest lightning density in the Samboja sub-district in 2019 with a value of 67.23 with land cover dominated by dry land mixed with shrubs. The high number of lightning strikes in these two areas is caused by humidity, resulting in accumulation of positive charge.